Development of Infant Reaching Strategies to Tactile Targets on the Face - Chinn, Lisa K.; Noonan, Claire F.; Hoffmann, Matej; Lockman, Jeffrey J. (Frontiers in Psychology, 2019)
Infant development of reaching to tactile targets on the skin has been studied little, despite its daily use during adaptive behaviors such as removing foreign stimuli or scratching an itch. We longitudinally examined the development of infant reaching strategies (from just under 2 to 11 months) approximately every other week with a vibrotactile stimulus applied to eight different locations on the face (left/right/center temple, left/right ear, left/right mouth corners, chin). Successfully reaching for the stimulus uses tactile input and proprioception to localize the target and move the hand to it. We studied the developmental progression of reaching and grasping strategies. As infants became older the likelihood of using the hand to reach to the target - versus touching the target with another body part or surface such as the upper arm or chair - increased. For trials where infants reached to the target with the hand, infants also refined their hand postures with age. As infants became older, they made fewer contacts with a closed fist or the dorsal part of the hand and more touches/grasps with the fingers or palm. Results suggest that during the first year of life infants become able to act more precisely on tactile targets on the face.